APPLICATION OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN DISSEMINATION OF INFORMATION IN SELECTED SPECIAL LIBRARIES IN ILORIN METROPOLIS, KWARA STATE, NIGERIA - Akanbi, Mohammed Lawal; Ogunleye, Dorcas Odunayo; Sulaiman, Kabir Alabi (Record and Library Journal, 2020)
Background of the study: This study examined the Application of ICT in Dissemination of Information in Selected Special Libraries in Ilorin Metropolis, Kwara State, Nigeria. Three Special libraries from the metropolis of the state comprised the sample population of the study; Central Bank of Nigeria Library, Michael Imoudu Institute of Labor Studies Library and Ghalib Chamber Library.Purpose: The study employed a survey research design using the Enumeration sampling technique. A questionnaire was used to obtain data from the respondents. The population of the study consisted of twenty-one (21) respondents which comprised of library professionals and library assistants.  The usage of Email to render CAS is not a norm in these special libraries.Method: Data collected from the field were analyzed using descriptive method of analysis.Findings: Apart from CAS, it was found that selective dissemination of information (SDI) is not done with the aid of technological tools in these Libraries and these libraries rarely make use of OPAC to provide easy access to their resources, efficiency and effectiveness of ICT in the dissemination of information were not realized because of the low usage of ICT to drive operations in the library. The study recommended that there should be a standard alternative source of power for proper Usage of ICT facilities and management of special libraries should help their users in subscribed for a database that would assist them in having access to robust information.Conclusion: The study concluded that ICT facilities are put in place in the selected special libraries are not adequate and are as well not fully utilized. It was gathered that the usage of ICT facilities to render services like current awareness services (CAS) is not up to expectation.